Effects of quercetin and daidzein on egg quality, lipid metabolism, and cecal short-chain fatty acids in layers - Liu, Jiayan; Liu, Junhong; Zhou, Shuaishuai; Fu, Yuxin; Yang, Qinglin; Li, Yao (Frontiers in Veterinary Science, 2023)
In this study, the effects of quercetin and daidzein on egg quality, lipid metabolism, and cecal short-chain fatty acids (SCFAs) were compared in layers. Hyline brown layers at 385 days of age with a similar laying rate (81.36% ± 0.62%) and body weight (2.10 kg ± 0.04 kg) were randomly divided into three treatments, six replicates per treatment, and 20 layers per replicate. Layers in control, quercetin, and daidzein treatment were fed by a basal diet supplemented with 0 mg/kg, 500 mg/kg quercetin, and 30 mg/kg of daidzein for 10 weeks. Results showed that eggshell strength and albumen height in week 4, egg yolk diameter in week 10, and eggshell thickness and egg yolk height in weeks 4 and 10 were significantly increased in the quercetin treatment (P ≤ 0.05); contents of phospholipid (PL) and lecithin (LEC) in egg yolk and high-density lipoprotein (HDL) content in serum were significantly increased; however, contents of malondialdehyde (MDA), total cholesterol (TC), and triglyceride (TG) in egg yolk, contents of TC, TG, low-density lipoprotein (LDL), and very-low-density lipoprotein (VLDL) in serum, and contents of TC and TG in the liver were significantly decreased in the quercetin treatment (P ≤ 0.05); contents of isobutyric acid and valeric acid were significantly increased in the cecum of the quercetin treatment (P ≤ 0.05), compared with control. Moreover, egg yolk height in week 10 and eggshell thickness in weeks 4 and 10 were significantly increased in the daidzein treatment (P ≤ 0.05); contents of MDA, TC, and TG in egg yolk, TC, TG, and VLDL in serum, and TC and TG in liver were significantly decreased in the daidzein treatment (P ≤ 0.05); and HDL content was significantly increased in serum of the daidzein treatment (P ≤ 0.05) compared with control. However, daidzein did not affect SCFA content in the cecum. In conclusion, egg quality was improved by quercetin and daidzein by increasing the antioxidant ability of egg yolk and by regulating lipid metabolism in layers. Quercetin worked better than daidzein in improving egg quality under this experimental condition.